2012
DOI: 10.1103/physreva.86.022110
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Zeno effect for sharply localized atomic states

Abstract: We analyze the nonquadratic in time Zeno effect which arises when a few-atom state initially trapped between two high laser-induced barriers is briefly released to free evolution. We identify the Zeno time, analyze the energy distributions of those atoms which have escaped and those that remained inside the trap, and obtain a simple relation between the survival and nonescape probabilities. The relevant time scales are such that the effect would be observable for the atomic species used in current laser experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
(25 reference statements)
4
12
0
Order By: Relevance
“…Further study of the characterization of initial states is needed [32]. It is also worth mentioning that a nonquadratic t 3/2 short-time behavior does not prevent the occurrence of the quantum Zeno effect [4,13,15]. Finally, we believe that our results may be relevant for quests regarding the description of the short-time behavior of unstable systems in relativistic quantum field theory where it has been found that the second moment to the Hamiltonian diverges [33].…”
Section: Discussionmentioning
confidence: 72%
“…Further study of the characterization of initial states is needed [32]. It is also worth mentioning that a nonquadratic t 3/2 short-time behavior does not prevent the occurrence of the quantum Zeno effect [4,13,15]. Finally, we believe that our results may be relevant for quests regarding the description of the short-time behavior of unstable systems in relativistic quantum field theory where it has been found that the second moment to the Hamiltonian diverges [33].…”
Section: Discussionmentioning
confidence: 72%
“…Experimentally, it was first demonstrated in [11] and its existence sets the ground for the quantum Zeno effect [12]. It is a consequence of unitary time-evolution, provided that the first and second moments of the Hamiltonian exist, see [13,14] for exceptional cases. That deviations from exponential decay are as well to be expected at long times was pointed out by Khalfin in 1957, for systems whose energy spectrum is bounded from below [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, we also note that this short-time behavior relies on the existence of the second moment of the Hamiltonian and deviations are expected whenever energy fluctuations diverge, even under unitary dynamics. For example, a fractional exponent 3/2 has been reported in the early decay of the survival probability of sharply localized wavepackets undergoing free evolution [24].…”
Section: B Short-time Nonexponential Decaymentioning
confidence: 99%